2011
DOI: 10.1371/journal.pone.0024649
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Strawberry FaASR Gene in Relation to Fruit Ripening

Abstract: BackgroundABA-, stress- and ripening-induced (ASR) proteins have been reported to act as a downstream component involved in ABA signal transduction. Although much attention has been paid to the roles of ASR in plant development and stress responses, the mechanisms by which ABA regulate fruit ripening at the molecular level are not fully understood. In the present work, a strawberry ASR gene was isolated and characterized (FaASR), and a polyclonal antibody against FaASR protein was prepared. Furthermore, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 83 publications
(143 reference statements)
1
48
0
1
Order By: Relevance
“…The Asr1 orthologs have been extensively described as functionally involved in stress responses. In a wide variety of species, including strawberry, 15 conditions in a wide range of species. Among others, this increase occurs in tobacco and tomato by osmotic and drought stress; 4,16,[20][21][22] in rice by drought, saline and osmotic stress; 10,23,24,25 and in plantain and banana by osmotic and biotic stress.…”
Section: Functional Roles Of Asr1mentioning
confidence: 99%
See 1 more Smart Citation
“…The Asr1 orthologs have been extensively described as functionally involved in stress responses. In a wide variety of species, including strawberry, 15 conditions in a wide range of species. Among others, this increase occurs in tobacco and tomato by osmotic and drought stress; 4,16,[20][21][22] in rice by drought, saline and osmotic stress; 10,23,24,25 and in plantain and banana by osmotic and biotic stress.…”
Section: Functional Roles Of Asr1mentioning
confidence: 99%
“…13,31 However, ASR1 is also expressed under many other physiological conditions, such as tomato and strawberry fruit ripening. 3,4,15 This indicates that ASR1 may have other functions beyond its role in stress. More than a decade ago,Çakir et al 17 proved that a grape ASR1 ortholog called MSA recognizes specific sites in the regulatory region of the hexose transporter 1 gene (Ht1 is described in Hayes et al 37 Vignault et al 38 and Fillion et al).…”
Section: Functional Roles Of Asr1mentioning
confidence: 99%
“…Several Asr orthologous and paralogous genes have been found to be transcriptionally regulated by ABA and sugars (Amitai-Zeigersona et al, 1995;Rossi et al, 1998;Çakir et al, 2003;Kalifa et al, 2004a;Liu et al, 2010;Chen et al, 2011;Henry et al, 2011;Virlouvet et al, 2011). Furthermore, a model for VvMSA transcriptional regulation at the convergence of Glc and ABA signaling cascades through HEXOKINASE1 and SnRK1 has recently been proposed (Saumonneau et al, 2012).…”
mentioning
confidence: 99%
“…ASR proteins have been shown to possess transactivation activities and chaperone-like activity (Çakir et al 2003;Kalifa et al 2004;Konrad and Bar-Zvi 2008;Dai et al 2011;Hsu et al 2011;Ricardi et al 2012;Hu et al 2013). Functional analysis revealed that ASRs were involved in plant development, fruit ripening, senescence, and response to various abiotic stresses (Huang et al 2000;Chen et al 2011;Yang et al 2005;Hu et al 2013;Liu et al 2013;Arenhart et al 2013a, b). Recently, more important lines of evidence showed that tomato ASR1 can target with cell wall synthesis and aquaporin genes under osmotic conditions (Ricardi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several orthologous and paralogous ASR genes have been found to be transcriptionally regulated by ABA and sugar signaling (Amitai-Zeigersona et al 1995;Çakir et al 2003;Kalifa et al 2004;Liu et al 2010;Chen et al 2011;Henry et al 2011;Virlouvet et al 2011;Joo et al 2013). Additionally, overexpression of some ASR genes resulted in reduced sensitivity to ABA and changed transcription levels of ABA/ stress-responsive genes (Yang et al 2005;Shkolnik and BarZvi 2008).…”
Section: Introductionmentioning
confidence: 99%